Classification and separation of sources of qualitative composition of chick-pea collections by the content of protein and olive - Пузік, В. К.; Тітова, А. Є. (Scientific Progress & Innovations, 2018)
The results of four-year studies of chick-pea (Cicer L.) collection (the biochemical analysis of the protein content according to Kel’dall's method and the oil content according to Rushkovsky's method) are summarized. 30 samples of chick-pea, 7 species – Cicer arientinum L., C. Reticulatum Labizinsky, C. Judaicum Boiss, C. bilugum K.N. Rech., C. Pinnatifidum Jaub., C. chorassinicum (Bge) M. Pop., C. Yamashitae Kitam are studied. The features of protein and oil content variability in the collection samples under different weather conditions during the years of chick-pea growth in the Eastern Forest-Steppe of Ukraine are analyzed. A structural analysis of the collection was carried out for isolation the sources of high protein and oil content with the view of the further creation of a new base line for chick-pea breeding. Samples with high stability of protein content by years were single out: the least standard deviation of the index and the coefficient of variation were among the cultivar C. arientinum L. UD0500001 (Iran), among the six wild species the same characteristics occur in the case of the species C. bilugum K. N. Rech ICCW42 (Turkey). The coefficient of variation in the collection over the research years ranged from 2.1 % to 9.8 %, which indicates the high stability of this feature in terms of research years. Donor samples of high content of oil have been single out. In years with wet weather the protein content is lower than that of years with arid weather in all collection samples. We took notice of samples value that showed a relatively high level of protein or oil on average over the research years. Such samples can be considered as a source of high content of protein or oil in the conditions of the Eastern Forest-Steppe zone of Ukraine. The main task of chick-pea breeding is to produce varieties with increased productivity, which are characterized by high taste and high content of the most valuable amino acids, resistant to fungal, bacterial and viral diseases, and also suitable for mechanized harvesting. Study of the source material for breeding under different environmental conditions allows to establish the rate of reaction of different genotypes to these conditions more accurately and makes it possible to prognosis their practical use. An integrated approach to breeding is a modern requirement for the creation of varieties not with one, but with a number of signs resistant to environmental conditions. Chick-pea is an important leguminous culture with high protein content, which is important for a balanced diet of humans.